INDUSTRY 5.0 AND OPPORTUNITIES FOR USING ARTIFICIAL INTELLIGENCE IN BUSINESS PROCESS MANAGEMENT - Eshankulov Azamkhon; Mannanova Shakhida Gaibullayevna (Journals Park Publishing, 2025)
The article summarizes various scientific data to determine how artificial intelligence and advanced digital technologies interact and how they contribute to the advancement of Industry 5.0 to a new level of industrial development. In line with the Industry 5.0 paradigm, the research aims to explore the revolutionary effects of combining cutting-edge digital technologies and artificial intelligence in intelligent manufacturing. The problem is that in today's economic conditions, we are not yet ready to fully entrust business process management, and even more so the decision-making procedure, to artificial intelligence. The article presents a new vision of the results of using advanced digital technologies combined with artificial intelligence, the interaction of which allows you to increase productivity, efficiency and efficiency of business process management. The results presented in this article will be of interest to companies seeking to use advanced digital technologies and artificial intelligence to optimize business processes and increase production productivity.
Keywords: Industry 5.0, advanced digital technologies, artificial intelligence, intelligent manufacturing, business processes.